Transformative Interaction Capability on Teamwork Performance: Strategies or Challenges? Perspective On Merchant Marine College - Pambudi Widiatmaka; Sukirno Sukirno; Ali Muktar Sitompul; Fitri Kensiwi; Hartoyo Hartoyo; Kundori Kundori; Haniek Listyorini; Sukrisno Sukrisno; Hartoyo soehari; Pranoto Pranoto; Karona Cahya Susena (UNIVED Press, 2024)
This study aims to build a new conceptual model based on the novelty produced by previous researchers called Transformative Interaction capability. Transformative interaction capabilities are expected to resolve the results of research between frequent and team performance. Structural study methodology was adopted in this study and a sample of 260 samples was taken from analysis units spread throughout Indonesia as a Merchant marine college. Data collection was carried out using a questionnaire and data analysis was carried out using Amos 25. The findings in this study indicate that there is a strategic path to improve the performance of the public organization team at the Merchant marine College. There are two ways to improve team performance. The strategy includes transformative interaction capabilities to improve team performance. The results of this study bring benefits for theoretical and practical development.